Pemberdayaan Pemuda Desa Tunjung melalui Pelatihan Desain Grafis dan Branding Berbasis Aplikasi Canva - Beny Riswanto; Ridwan Zulkifli (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
his community service program aims to empower youth in Tunjung Village through training in graphic design and branding using the Canva application. The training responds to the limited design skills among local youth, despite their basic knowledge of digital devices. In the digital era, the ability to produce visually appealing content is essential for promoting local products, supporting micro-enterprises, and enhancing community activities. The program was implemented using an Action Research (AR) approach, consisting of three main stages: preparation, implementation, and evaluation. The results showed a significant improvement in participants’ abilities to use Canva in designing various visual materials such as posters, banners, and logos. Despite several technical obstacles, such as limited device availability and unstable internet access, the training ran effectively. Final evaluations indicated positive responses from participants, who found the materials beneficial in enhancing their digital literacy and entrepreneurial potential. This initiative contributes to strengthening youth capacity in utilizing technology for productive and creative purposes.